Intervensi Rehabilitasi Stroke: Tinjauan Komprehensif tentang Intervensi Berbasis Komunitas - Julika Siagian, Heriviyatno; Tukatman, Tukatman (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Community-based interventions are very important to facilitate post-stroke recovery, increase community participation, and increase awareness about stroke survivors. To optimize recovery and community reintegration, there is a need to understand research findings on community-based interventions that focus on stroke survivors and their caregivers. Although nurses and community health workers are commonly involved in community-based interventions, little is known about their role compared to other post-stroke rehabilitation professionals (physical therapists, occupational therapists, and speech-language pathologists). Therefore, the aim of this review is to explore research that focuses on improving community-based stroke recovery for adult stroke survivors, caregivers, or both when provided by nurses or cadres. A systematic review using Scopus, PubMed, Medline, Cochrane Library, Proquest, and Embase was completed to identify community-based post-intervention studies using nurses or community health workers up to February 2024. Eighteen studies meeting inclusion criteria from 9 countries were identified. Details regarding the role of nurses and public health cadres are limited or not discussed. The intervention emphasizes stroke survivor self-care and caregiver support and is offered face-to-face and in group sessions in the community and home. A variety of instruments are used to measure outcomes. The results of the interventions provided were mixed. Improvements were seen in perceived health, quality of life, knowledge, self-efficacy, self-management, and caregiver support. Nurses and community health workers play an important role in community-based care. Evidence shows that community-based interventions facilitate the necessary support for stroke survivors, caregivers, families, and communities to optimize stroke recovery. Data from this review illustrate the ongoing need for comprehensive programs designed to meet the complex needs of stroke survivors and families when they return to their homes and communities.